HYDROCARBON RESERVOIR STATIC MODELLING OF SB-1 TO MFS-2 INTERVAL IN SANTUL FORMATION, SEHA FIELD, TARAKAN BASIN, NORTH KALIMANTAN. - Wildan, Syafiq
Seha Field is a field located in North Kalimantan that is proven to produce hydrocarbon. This field is in Tidung Sub-basin, one of four sub-basin which is the part of Tarakan Basin. This study will focus on Santul Formation, bounded between SB-1 and MFS-2, on five gas reservoir intervals. This study has a goal to learn about the geological condition, to model the reservoir geometry and property, and to estimate the volume of hydrocarbon reserves (which is gas) in five reservoir interval of Santul Formation, Tarakan Basin. This study uses well datas, cutting description datas, biostratigraphy analysis data, DST datas, and 2D seismic datas. This study uses methods like stratigraphy sequence correlation, facies analysis, reservoir thickness analysis, petrophysical analysis, depositional environment analysis, well-seismic tie, creating time and depth structure map, three-dimensional structure modelling, petrophysical modelling, and hydrocarbon reserve calculation. These methods will show the results of geological condition of study area. Depositional environment analysis shows that five reservoirs are wave-dominated estuary. There are structures involvement like anticline, normal fault, and reverse fault. The anticline’s axis is northwest - southeast. These faults have northeast – southwest and northwest-southeast trend. It is known that the age of these anticline and faults is Plio-Pleistocene and was caused by sinistral strike-slip regime with northwest – southeast trend. Petrophysical analysis results show that the interval of study area is shaly sand. The reservoirs have shale volume mean 40%, porosity mean 17%, and water saturation mean 70%. Hydrocarbon volume estimation in five reservoirs was done in a segment and has hydrocarbon volume total in 72.4 bcf.